WHAT DO INNOVATIVE SCHOLS DO WITH TECHNOLOGY?: ICT SERVING THE SCHOOL AND THE COMMUNITY IN THE AMARA BERRI SCHOOL - José Miguel Correa Gorospe; Asunción Martínez Arbelaiz (Ediciones Universidad de Salamanca, 2010)
<!-- @page { margin: 0.79in } P { margin-bottom: 0.08in } --> The use of digital technologies requires careful thinking that organizes and guides their integration into school activities. ICT (Information and Communication Technologies) have a recognized potential but their actual impact has serious limitations. The analysis of good practices with ICT has been developed within the research project entitled "Analysis of educational policies regarding ICT in schools and their effects on pedagogical innovation in the Basque Country" and it has made us pay special attention to the use of digital technologies in the Colegio Amara Berri from San Sebastián, a school with a long and well-deserved reputation for innovation. We describe the activities in the department of Mass Media (Hedabideak), its different workshops and their organization, its tasks and projects, as well as the roles of teachers and students. Finally, we end up assessing the experience from a pedagogical point of view.